Faktor-Faktor Yang Mempengaruhi Pedagang Pasar Dalam Menggunakan Pembiayaan Mikro iB Pada Bank Syariah Indonesia Kantor Cabang Bekasi - Adinda, Sri; Fahlevi, Rizal (At-Tamwil: Journal of Islamic Economics and Finance, 2024)
This research aimed to find out how the influence of product knowledge, consumer behaviour and service of BRI Syariah Bank employees on the interest of Bekasi traditional market traders in using Mikro iB financing. Respondents in this research were 60 market traders located in the Bekasi City area in the period January - February 2020. Method this research is quantitative research to examine the effect of independent variable on the dependent variable. The analysis technique used is multiple linear regression. The results of this study found that product knowledge, consumer behaviour and bank services have a positive and significant on the interest of Bekasi market traders in using Sharia Micro IB financing. simultaneously product knowledge, consumer behaviour and bank services affect the interest of bekasi market traders in using Sharia Mikro iB financing market in using Sharia Mikro iB financing.